PENGARUH STRES KERJA, KOMUNIKASI, KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA KANTOR PERTANAHAN KOTA SURABAYA II - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The research aims to find out the effect of work stress, communication, work ability on employee performance through job satisfaction at surabaya land office. The population and samples in this study were employees at the Surabaya II Land Office as many as 100 respondents. This research is a type of explanatory research, and quantitative approach. Data analysis techniques using PLS Vers.3.0. The results of the study showed that work stress did not directly affect job satisfaction at the Surabaya II Land Office. Communication directly affects job satisfaction at the Land Office of Surabaya II. Work ability directly affects job satisfaction at the Surabaya II Land Office. Work stress directly affects employee performance at the Surabaya II Land Office. Communication directly affects the performance of employees at the Surabaya City Land Office II. Work capability directly affects employee performance at the Surabaya II City Land Office. Job satisfaction directly affects employee performance at the Surabaya II Land Office. Work stress does not have an indirect effect on employee performance through job satisfaction at the Surabaya II City Land Office II. Communication affects indirectly on employee performance through job satisfaction at the Surabaya II City Land Office. Work ability does not affect indirectly on employee performance through job satisfaction at the Surabaya Ii Land Office.